Pengaruh Pengembangan Karir Dan Kompetensi Terhadap Kepuasan Kerja Yang Berdampak Pada Kinerja Pegawai Negeri Sipil Dinas Kelautan Dan Perikanan Provinsi Jawa Barat - Dion Alan Nugraha; Banuara Nadeak; Nelly Martini; Dede Jajang Suyaman (Islamic University of Kalimantan MAB Banjarmasin, 2022)
Career competence, competency, and work happiness all help the Office of Marine Affairs and Fisheries of West Java Province function better. This study will explore the effect of both partially and concurrently on employee performance improvement mediated by work satisfaction. This research is quantitative and uses path analysis together with multiple regression and mediation models to verify and analyze data. This research used Proportionate Random Sampling to choose 143 employees from a total population of 222. The results revealed that career advancement has a 36.78 percent influence on work satisfaction. Competence has a 2.75 percent effect on work satisfaction. Career development has a 31.63 percent impact on employee performance. Competence influences employee performance by 0.0398 or 3.98 percent. Job happiness has an 8.18 percent impact on employee performance. a combined impact of 0.4378 or 43.78 % This suggests that career growth and competency characteristics contribute 43.78 percent to work satisfaction, while the remainder contributes 56.22 percent.